Introducing Procedural Utility: Not only What, but also How Matters - Bruno S. Frey; Matthias Benz; Alois Stutzer (Center for Research in Economics, Management and the Arts (CREMA), 2003)
People not only care about outcomes, they also value the procedures which lead to the outcomes. Procedural utility is a potentially important source of human well-being. This paper aims at introducing the concept of procedural utility into economics, and argues that it should be incorporated more widely into economic theory and empirical research. Three building blocks of a concept of procedural utility are outlined and it is suggested how procedural utility can be fruitfully integrated. Evidence from a broad range of social sciences is reviewed in order to show that procedural utility is a relevant concept for economics.
Keywords: A00; A12; D60; D70; 330; procedural utility; outcome utility; institutions